Analysis of implementation outcomes of quality improvement initiatives in Haiti: the fingerprint initiative. - Demes, Joseph Adrien Emmanuel; Becerril-Montekio, Victor; Torres-Pereda, Pilar; Jasmin, Ernst Robert; Geto Dube, Jean; Garcia Coq, Jean; Nickerson, Nathan (Pan American Journal of Public Health, 2021)
Objective. To assess the process and outcomes of the implementation of an electronic fingerprint initiative as part of quality improvement in three health facilities in the Northern Department of Haiti, in terms of its acceptability, adoption, feasibility, fidelity, and sustainability. In Haiti, poor attendance of the healthcare workforce is a nationwide problem, closely related to the quality of care. Three health institutions have tried to implement an electronic fingerprint system to monitor and improve attendance. Methods. An exploratory and qualitative descriptive study of the implementation outcomes of the fingerprint initiative. It was based on semi-structured interviews and one group discussion using purposeful sampling techniques to recruit participants, and an open coding system and deductive approach to analyze the data using ATLAS.ti 8. Results. The fingerprint initiative was successfully implemented in a non-governmental organization supported health facility but, despite some planning, it was never implemented in the public health facilities. The acceptability of the implementation was high in the not-for-profit organization and low in the public settings, mostly in relation to the presence of champions and the leadership at each health facility. Conclusions. We recommend more involvement of the leadership of health facilities in the different phases of the implementation process in order to guarantee acceptability, adoption, fidelity and sustainability. More research is needed to articulate this technology-driven initiative in the Haitian health system.